AN ANALYSIS OF TRANSLATION TECHNIQUE IN TRANSLATING NARRATIVE TEXT - Saud Jefriyanto; Zulkifli La Samidi (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2018)
The present work is an analysis of translation technique in translating narrative text. Ingeneral, there are many aspects of translation techniques that can be discussed, nor in thisresearch the researcher only use eight techniques such as literal translation, idiom translation,calque translation, etc. Moreover, the purpose of this research is to investigate the product oftranslation English to Indonesian from the students of English Department 2013 intranslating Narrative text and analyzed it by using eight techniques in translating it. The datain this research is carried out by using qualitative method. This research reveals that thedominant technique that the participants use is borrowing technique, by amounting about 37times. Meanwhile, the less dominant technique that the participants use is transpositiontechnique by amounting about 7 times. Furthermore, those participants prefer to useborrowing technique it is because they believe that it is more familiar diction and easy forthe readers to understand the text.